The Clinical Efficacy and Safety of 11 Commonly Used Treatment Strategies Improving Arrhythmia of CHD in China: A Network Meta-Analysis - Wang, Tao; Li, Wei; Huang, Qianqian; Yuan, Chuqiao; Qu, Liping; Xiao, Xiaohe; Zou, Wenjun (Frontiers in Pharmacology, 2021)
Purpose: Arrhythmia which as a common complication of CHD, has a high incidence. At present, more and more anti-arrhythmic drugs are used in clinical practice. However, which drug has the best efficacy and high safety is still unknown. Therefore, we decided to use NMA to solve this problem. Method: We searched CNKI, Wanfang database, VIP database, Pubmed, Embase and Cochrane libraries, and collected all RCTs of arrhythmia of CHD, and used RevMan (5.3) and Stata (13.0) to carry out this NMA. The primary outcome indicator of this study is efficiency; the secondary outcome indicator is the incidence of adverse reactions. Result: A total of 134 RCTs, 13951 patients, and 11 treatment strategies were included in this NMA. The results show that all treatment strategies can effectively improve the arrhythmia of patients. Among them, PMA+AM, AM+AT, AM+WG have higher effective rates, and PMA+AM, WG+ME, SC+ME have better safety. The effectiveness and safety of the treatment strategies which combined TCM and chemical drugs, are significantly better than that of using chemical drugs alone. Conclusion: The treatment strategy of combination of multiple drugs usually has higher efficiency and safety. PMA+AM seems to be the most recommended treatment strategy. In addition, TCM has great potential in improving the efficacy and safety of chemical drugs.